2003
DOI: 10.3748/wjg.v9.i7.1394
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1, GSTs and mEH polymorphisms and susceptibility to esophageal carcinoma: Study of population from a high- incidence area in north China

Abstract: The present results suggest that CYP1A1 3' polymorphism may be one of the promising protective factors and its wild gene type may be an indicator for higher susceptibility to esophageal cancer. mEH slow allele variant, associated with the progression of esophageal precancerous lesions, may contribute to the high susceptibility to esophageal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 14 publications
1
44
2
Order By: Relevance
“…No results have been thus far reported for association between EPHX1 activity and gastric cancer. Interestingly, a marked decreased risk for slow EPHX1 activity has been often observed for respiratory tumors strongly related to smoking, such as lung (35) and larynx (36), whereas an increased risk for slow activity has been reported for digestive tumors, such as esophagus (37) and colorectal adenoma (38), the latter was significant only among smokers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…No results have been thus far reported for association between EPHX1 activity and gastric cancer. Interestingly, a marked decreased risk for slow EPHX1 activity has been often observed for respiratory tumors strongly related to smoking, such as lung (35) and larynx (36), whereas an increased risk for slow activity has been reported for digestive tumors, such as esophagus (37) and colorectal adenoma (38), the latter was significant only among smokers.…”
Section: Discussionmentioning
confidence: 96%
“…36 Metabolic gene allele nomenclature according to that recommended by Garte et al (11) is also provided. 37 Other Factors. Subjects were classified according to smoking habit at recruitment as current, former, or never smokers of any type of tobacco products, although the majority of them smoked cigarettes exclusively or in addition to cigars and/or pipe.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Wang et al (2003) found cases with CYP1A1 Ile/Val polymorphism had no significant difference of developing esophageal squamous cell carcinoma compared to controls in Northern China. A study of Wang et al (2002a) .…”
Section: Discussionmentioning
confidence: 51%
“…Guo et al (2005) found that individuals with the MspI T/C or C/C genotype had a higher risk of developing esophageal cancer than those with the T/T genotype (OR:1.93,95%CI:1.01-3.84). However, the study results of Wang et al (2003) suggested that the genotype of MspI T/C (OR:0.41,95%CI:0.17-0.99) or (T/C+C/C) (OR:0.41,95%CI:0.17-0.99) might be protective factor for developing esophageal cancer. The heterozygosis genotype T/C of CYP1A1 MspI genetic polymorphism was found to be associated with elevated esophageal cancer risk in the study of van Lieshout et al (1999).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation